PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK PADA PEMBELAJARAN IPAS MATERI TUMBUHAN SUMBER KEHIDUPAN DI BUMI KELAS IV SDN 02 NGADIWARNO - Khusnul Khotimah Wulandari; Ferina Agustini; Choirul Huda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the limitations of media and monotonous learning methods in the applied learning process, especially in science learning. The purpose of this research is to develop pop up book learning media in science learning on the topic